2006
DOI: 10.1007/s10665-006-9054-1
|View full text |Cite
|
Sign up to set email alerts
|

The linear-wave response of a periodic array of floating elastic plates

Abstract: The problem of an infinite periodic array of identical floating elastic plates subject to forcing from plane incident waves is considered. This study is motivated by the problem of trying to model wave propagation in the marginal ice zone, a region of ocean consisting of an arbitrary packing of floating ice sheets. It is shown that the problem considered can be formulated exactly in terms of the solution to an integral equation in a manner similar to that used for the problem of wave scattering by a single ela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
1
12
0
Order By: Relevance
“…We have shown how to efficiently calculate the slowly convergent series which arise in this formulation and how to determine the scattered field far from the array in terms of the amplitudes in the cylindrical eigenfunction expansion. Our numerical results agree with those presented in Linton & Evans (1993) and Wang et al (2005). We have also presented results for the case of fixed, rigid and flexible arrays of bodies of negligible draft.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…We have shown how to efficiently calculate the slowly convergent series which arise in this formulation and how to determine the scattered field far from the array in terms of the amplitudes in the cylindrical eigenfunction expansion. Our numerical results agree with those presented in Linton & Evans (1993) and Wang et al (2005). We have also presented results for the case of fixed, rigid and flexible arrays of bodies of negligible draft.…”
Section: Discussionsupporting
confidence: 86%
“…Due to the axisymmetry, they are particularly simple. In fact, they are diagonal with diagonal elements Next, we compare our results to those of Wang et al (2005) who considered the waterwave scattering by an infinite array of floating elastic plates in water of infinite depth. The plates were modelled in exactly the same way as our elastic plates in §8.…”
Section: Comparison With Results From Linton and Evans (1993)mentioning
confidence: 99%
See 1 more Smart Citation
“…Note that, in the short-circuit limit ξ → 0, the second term inside the brackets at the left-hand side of (3.23) vanishes. Within this limit, the fifth derivative of the velocity potential in (3.23) is multiplied only by the non-dimensional stiffness β and the resulting boundary-value problem is equivalent to that of a submerged elastic plate without power extraction [22][23][24][25], as expected. Indeed, the complex coefficient α 2 ωξ/(i + ωξ) in (3.23) is a dissipative term which models the extraction of energy from the system by means of the resistive circuits of figure 2.…”
Section: Solution Of the Coupled Systemmentioning
confidence: 99%
“…They considered the effect of the partition walls on the wave motion and found that the partition walls might lead to several reflected waves traveling in different directions. This interesting phenomenon also exists in wave scattering by other periodic coastal structures [25][26][27][28][29]. A review on water wave interaction with periodic structures can be found in McIver [30].…”
Section: Solid Wallmentioning
confidence: 85%